Isotactic Polypropylene/Multi‐Walled Carbon Nanotube Nanocomposites: The Effect of Modification of MWCNTs on Mechanical Properties and Melt Crystallization. Issue 21 (18th September 2013) - Papageorgiou, George Z.; Nerantzaki, Maria; Grigoriadou, Ifigeneia; Papageorgiou, Dimitrios G.; Chrissafis, Konstantinos; Bikiaris, Dimitrios
<x xml:space="preserve">Abstract</x> Nanocomposites of isotactic polypropylene (iPP) containing modified multi‐walled carbon nanotubes (MWCNTs) are prepared by melt mixing. MWCNTs with alkyl groups (alkyl‐MWCNTs) and with methyl‐PEG (mPEG‐MWCNTs) are used, as well as unmodified MWCNTs, to prepare the three series of nanocomposites. The surface treatment and the content of MWCNTs affect the mechanical properties of the iPP. In all cases, theoretical models are used to estimate the effect of surface treatment. The crystallization rates of nanocomposites in both isothermal and non‐isothermal crystallization conditions are measured. The nanocomposites containing unmodified MWCNTs crystallize faster than those with modified MWCNTs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>